It's mine! - Lionni, Leo, 1910-1999. (New York : Knopf : Distributed by Random House, 1986)
Three selfish frogs quarrel over who owns their pond and island, until a storm makes them value the benefits of sharing.
G2
Keywords: Selfishness -- Fiction; Sharing -- Fiction; Frogs -- Fiction